BLOWING EXERCISE IN INCREASING LUNG CAPACITY IN CHILDREN WITH LUNG DISEASE: SYSTEMATIC REVIEW - Syaiful, Afifah Ayu (Universitas Aisyah Pringsewu, 2023)
Diseases of the lungs and airways are the most common conditions in the world, which can cause problems not only in the respiratory organs, but also abnormalities in the body's organ systems due to impaired air exchange during the breathing process. Infectious causes of lung and respiratory tract disease originate from bacterial, viral, fungal and parasitic infections, such as tuberculosis and pneumonia. Non-communicable causes of lung and respiratory diseases, originating from cigarettes or cigarette smoke, including pollution and hazardous materials, as well as genetics, such as COPD, asthma and lung cancer. The objective of this systematic review is to analyze blowing exercise by increasing lung capacity in children with lung disease. Methods used in compiling systematic reviews with electronic searches: ProQuest, ScienceDirect, SpingerLink, and SAGE Journals. The writing criteria are full text, keywords, abstract and publications in the 2019-2023 period. The research search found 11 articles that had been extracted. The results obtained, namely blowing exercise to increase lung capacity in children with pneumonia, have received a positive response and need to be developed dynamically.